Pengaruh Klon Kopi dan Dosis Urea pada Pertumbuhan Tanaman Kopi Robusta (Coffea canephora L.) di Kebun Entres - Iqbal, M. Bagas Nur; Same, Made; Hartono, Joko S. S. (Politeknik Negeri Lampung, 2023)
Coffee is one of the productive agro-industries in Indonesia, so care needs to be taken to use varieties and doses of fertilizers based on plant needs and environmental conditions. This study aimed to determine the clone, dose of urea, and the interaction between the clone and the dose for Robusta coffee plants in the mother planting stock farm. This study used a split-plot design with coffee clones as the main plot and doses of urea fertilizer as subplots. The study showed no significant difference between clones in the growth of robusta coffee plants, where clone BP 534 was the best clone for plant growth. In addition, based on the study's results, the best interaction was obtained where the best interaction for increasing the number of leaves was between clone BP 936 and a dose of 15 g.plant-1. The interaction between clones and the best dose for increasing the height and number of branches was between clone BP 936 and dose 20 g.plant-1, and the interaction between clones and the best dose for plant stem diameter was between clone BP 358 and a dose of 20 g.plant-1.